The Implementation of Extracurricular Qur'an Lovers Students of SMA 1 (Pasisma) Towards Student Character Evaluation - Himmatur Rofi’ah; Erma Fatmawati; Sofyan Hadi (Universitas Nurul Jadid, 2025)
Extracurricular activities are organized with the aim of develop potential, talents, interests, abilities, personality, cooperation, and optimal student independence in order to support achievement national education goals. SMAN 1 Jember held a Lovers extracurricular Al-Qur'an for SMA 1 Students (PASISMA) which helps students discuss religious knowledge. The focus of the research examined in this thesis is: 1) How extracurricular planning for Al-Qur'an lovers for SMA 1 (PASISMA) students in Jember 1 State High School? 2) How is it implemented extracurricular Al-Quran lovers for SMA 1 (PASISMA) students at school State High School 1 Jember? 3) How do lovers evaluate extracurricular activities? Al-Qur'an for SMA 1 (PASISMA) students at State Senior High School 1 Jember? 4) How does the PASISMA extracurricular affect student evaluation? The purpose of this study is the same as its focus. The objectives of this research are same as the focus.The approach used in this research is research qualitative with descriptive research type and the results of this research: 1) extracurricular planning for Al Qur'an lovers for SMA 1 (PASISMA) students at State Senior High School 1 Jember namely preparing the tools used and preparing a schedule for every PASISMA extracurricular activity. 2) Implementation of extracurricular activities for lovers Al-Qur'an for SMA 1 (PASISMA) students at State Senior High School 1 Jember namely carrying out PASISMA extracurricular activities according to the schedule that has been provided determined, namely on Thursdays every week alternately, and do different processes and programs in each PASISMA extracurricular activity. 3) Extracurricular evaluation of Al-Qur'an lovers for SMA 1 (PASISMA) students at school State Upper Middle School 1 Jember, namely once every three months and also There are activities that are evaluated directly by the extracurricular supervisor PASISMA. 4) The influence of PASISMA extracurricular activities on student evaluation, namely Providing a positive impact on students who take part in this extracurricular.